A study on maternal and perinatal outcome in pregnancy with oligohydramnios: study from a tertiary care hospital, Karnataka, India - Nabapure, Shilpa; S., Rashmi P.; Prabhudeva, Prema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Oligohydramnios is described as a condition with decreased amniotic fluid volume relative to gestational age. It is a severe and common complication of pregnancy which is associated with increased maternal morbidity and adverse perinatal outcomes. This study was conducted to find out the significance of oligohydramnios in determining the maternal and perinatal outcome in pregnant women with oligohydramnios. Methods: The present study is a hospital-based study conducted in the department of obstetrics and gynecology, of SSIMS and RC Davanagere, during the period between August 2018 to April 2019. Detailed clinical history was taken, AFI was measured using Phelan’s four quadrant ultrasound technique. All the information was entered in the proforma and analyzed. Results: The mean age group of the study participants was 26.36±4.46 years. Majority (51.9%) of them were primigravida. Gestational age, birth weight and abnormal Doppler study were found to have an association with the perinatal outcome. Perinatal mortality in the present study was 4%. Conclusions: Oligohydramnios is a frequent occurrence in obstetrics and this condition requires intensive surveillance and proper antenatal care.